Resonance vibration interventions in the femur: Experimental-numerical modelling approaches. (December 2021) - Presas, Alexandre; Valentin, David; Deering, Joseph; Kampschulte, Marian; Yu, Bosco; Grandfield, Kathryn; Mele, Elisa; Biehl, Christoph; Krombach, Gabriele A.; Heiss, Christian; Bosbach, Wolfram A.
Abstract: Motive: External vibration excitation might be key to many novel non-surgical interventions for pathologies in the musculoskeletal system and in other parts of the human organism. Lack of understanding about vibration patterns, their controllability, and reproducibility are three limitations of ongoing research. This study establishes a bovine vibration model and animal model replacements for future research. Methods: We used biological samples ( n = 5 ) and one polyurethane sample of the bovine femur. Mechanical resonance was measured experimentally and analysed numerically by finite element method. Main results: The experiments obtained 5 distinct mode shapes for the biological sample set, with standard deviation < 7.5%. Finite element analysis of the biological samples can replicate experimental mode shape deflection. The use of polyurethane changes resonance character but results are also good approximations of the biological samples. Conclusions: A model of the bovine femur with consistent resonance behaviour is presented with alternatives (polyurethane and finite element analysis) that can serve in reducing the number of necessary biological samples. Future work will be to adapt results to human anatomy. Of clinical interest will be to influence bone pathologies such as post-surgical non-union, or bone functionality as part of haematopoiesis and endocrine secretion.